Variation of bacterial community assembly over developmental stages and midgut of Dermanyssus gallinae - Wu-Chuang, Alejandra; Hartmann, David; Maitre, Apolline; Mateos-Hernández, Lourdes; Frantová, Helena; Urbanová, Veronika; Obregon, Dasiel; Cabezas-Cruz, Alejandro; Perner, Jan (Microbial ecology, 2023)
Bacterial microbiota play an important role in the fitness of arthropods, but the bacterial microflora in the parasitic mite Dermanyssus gallinae is only partially explored; there are gaps in our understanding of the microbiota localization and in our knowledge of microbial community assembly. In this work, we have visualized, quantified the abundance, and determined the diversity of bacterial occupancy, not only across developmental stages of D. gallinae, but also in the midgut of micro-dissected female D. gallinae mites. We explored community assembly and the presence of keystone taxa, as well as predicted metabolic functions in the microbiome of the mite. The diversity of the microbiota and the complexity of co-occurrence networks decreased with the progression of the life cycle. However, several bacterial taxa were present in all samples examined, indicating a core symbiotic consortium of bacteria. The relatively higher bacterial abundance in adult females, specifically in their midguts, implicates a function linked to the biology of D. gallinae mites. If such an association proves to be important, the bacterial microflora qualifies itself as an acaricidal or vaccine target against this troublesome pest.
Keywords: kur domácí; Poultry Diseases; Functional prediction; infestace roztoči; Mites; Chickens; stadia vývoje; Bacteria; roztoči; nemoci drůbeže; Keystone taxa; Animals; ženské pohlaví; zvířata; Life Cycle Stages; Microbial networks; Female; Microbiome; Dermanyssus gallinae; Mite Infestations